Understanding the formation of the wavy edges in plants leaves - Mohamad Farhan Mohamad Mukhlis (Nanyang Technological University, 2020)
The study of plant behaviour and properties have resulted in various innovations in the engineering industry. Much research has been carried out to study the behavioural properties of plants at a cellular level as well as the formation of its structure, leading to the development of many notable inventions. However, few studied the formation of leaf structure and the effects of its mechanical properties on the pattern form, which will be the focus of this report. Leaf patterns are formed when plants undergo morphogenesis, where differential growth occur at the cellular level. To study the effects on mechanical properties and better understand the formation of the wavy edges pattern, simulations were performed on a model of a leaf and mechanical properties were varied to observe its effects. To duplicate the differential growth that the leaf undergoes, a thermal expansion process was applied to the leaf to allow for the formation of the wavy edge patterns. Results obtained showed that no wavy edges were formed using the original set of boundary conditions in the simulation. To induce the formation of the wavy edges, a new set of boundary conditions were applied. These resulted in the formation of wavy edges, but the data obtained from these results did not allow for any conclusive relations to be made between the mechanical properties and the formation of the wavy edges.